Human Milk Plasmalogens Are Highly Enriched in Long-Chain PUFAs. Issue 11 (12th October 2016) - Moukarzel, Sara; Dyer, Roger A; Keller, Bernd O; Elango, Rajavel; Innis, Sheila M
Abstract: Background: Human milk contains unique glycerophospholipids, including ethanolamine-containing plasmalogens (Pls-PEs) in the milk fat globule membrane, which have been implicated in infant brain development. Brain Pls-PEs accumulate postnatally and are enriched in long-chain polyunsaturated fatty acids (LC-PUFAs), particularly docosahexaenoic acid (DHA). Fatty acid (FA) composition of Pls-PEs in milk is poorly understood because of the analytical challenges in separating Pls-PEs from other phospholipids in the predominating presence of triacylglycerols. The variability of Pls-PE FAs and the potential role of maternal diet remain unknown. Objectives: Our primary objectives were to establish improved methodology for extracting Pls-PEs from human milk, enabling FA analysis, and to compare FA composition between Pls-PEs and 2 major milk phospholipids, phosphatidylcholine and phosphatidylethanolamine. Our secondary objective was to explore associations between maternal DHA intake and DHA in milk phospholipids and variability in phospholipid-DHA within a woman. Methods: Mature milk was collected from 25 women, with 4 providing 3 milk samples on 3 separate days. Lipids were extracted, and phospholipids were removed by solid phase extraction. Pls-PEs were separated by using normal-phase HPLC, recovered and analyzed for FAs by GLC. Diet was assessed by using a validated food-frequency questionnaire. Results: Pls-PE concentration in human milk was significantly higher in LC-PUFAs than phosphatidylethanolamine and phosphatidylcholine, including arachidonic acid (AA) and DHA. The mean ± SD concentration of AAs in Pls-PEs was ∼2.5-fold higher than in phosphatidylethanolamine (10.5 ± 1.71 and 3.82 ± 0.92 g/100 g, respectively). DHA in Pls-PEs varied across women (0.95–6.51 g/100 g), likely independent of maternal DHA intake. Pls-PE DHA also varied within a woman across days (CV ranged from 9.8% to 28%). Conclusions: Human milk provides the infant with LC-PUFAs from multiple lipid pools, including a source from Pls-PEs. The biological determinants of Pls-PE FAs and physiological relevance to the breastfed infant remain to be elucidated.